2013
DOI: 10.1002/humu.22273
|View full text |Cite
|
Sign up to set email alerts
|

RNA snp: Efficient Detection of Local RNA Secondary Structure Changes Induced by SNP s

Abstract: Structural characteristics are essential for the functioning of many noncoding RNAs and cis-regulatory elements of mRNAs. SNPs may disrupt these structures, interfere with their molecular function, and hence cause a phenotypic effect. RNA folding algorithms can provide detailed insights into structural effects of SNPs. The global measures employed so far suffer from limited accuracy of folding programs on large RNAs and are computationally too demanding for genome-wide applications. Here, we present a strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 73 publications
0
93
0
Order By: Relevance
“…For this reason, methods for predicting the impact of SNVs have historically focused on the high-yield category of non-synonymous coding SNVs. The existence of disease-associated synonymous mutations32,33 and nocoding variations with effects on lincRNA,34 miRNA,35,36 and promoters37,38 has produced interest in other types of mutations as well, but different tools will be needed to analyze these types of variations and such tools are comparatively still new and untested 3941…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, methods for predicting the impact of SNVs have historically focused on the high-yield category of non-synonymous coding SNVs. The existence of disease-associated synonymous mutations32,33 and nocoding variations with effects on lincRNA,34 miRNA,35,36 and promoters37,38 has produced interest in other types of mutations as well, but different tools will be needed to analyze these types of variations and such tools are comparatively still new and untested 3941…”
Section: Introductionmentioning
confidence: 99%
“…To analyze whether rs895819 might change the secondary structure or the free energy of pre-mir-27a, we used RNAsnp [18] and RNAfold [19] to demonstrate that neither the conformation (P dmax > 0.2) nor the free energy are affected. However, it has been reported that a variation in the precursors of a certain miRNA can affect the maturation process and modulate the expression of mature miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the effects of rs895819 on the transcript structure, we modelled the secondary structure of precursor pre-mir-27a (similar results were also obtained starting with the primitive pre-mir-27a sequence-data not shown) using the RNAsnp software [18] and RNAfold WebServer [19]. RNAsnp compares the vector of base pair probabilities derived for the RNA sequence with and without the SNP.…”
Section: In Silico Bioinformatics Analysismentioning
confidence: 91%
“…Other methods aim to assess fitness effects of mutations in other annotation classes including microRNAs (mrSNP [39]), non-coding RNAs (RNAsnp [40]), and splice sites (SNPlice [41]). Most of these predictive methods can be implemented in plants and it should become possible to pre-compute exhaustively the effects of all possible mutations in each of these effect classes in well-annotated plant genomes [42].…”
Section: Characterizing Fitness Effects By Functional Effect Classmentioning
confidence: 99%